2022
DOI: 10.1021/acs.est.2c04324
|View full text |Cite
|
Sign up to set email alerts
|

Selective Methylation by an ArsM S-Adenosylmethionine Methyltransferase from Burkholderia gladioli GSRB05 Enhances Antibiotic Production

Abstract: Arsenic methylation contributes to the formation and diversity of environmental organoarsenicals, an important process in the arsenic biogeochemical cycle. The arsM gene encoding an arsenite (As(III)) S-adenosylmethionine (SAM) methyltransferase is widely distributed in members of every kingdom. A number of ArsM enzymes have been shown to have different patterns of methylation. When incubated with inorganic As(III), Burkholderia gladioli GSRB05 has been shown to synthesize the organoarsenical antibiotic arsino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Other ArsM orthologs have only A and B domains, and some of those methylate both As­(III) and MAs­(III), while others methylate only MAs­(III). For example, Figure shows a model of a typical three-domain ArsM, Burkholderia gladioli BgArsM . The radical SAM enzyme BgArsL forms reduced AST-OH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other ArsM orthologs have only A and B domains, and some of those methylate both As­(III) and MAs­(III), while others methylate only MAs­(III). For example, Figure shows a model of a typical three-domain ArsM, Burkholderia gladioli BgArsM . The radical SAM enzyme BgArsL forms reduced AST-OH.…”
Section: Resultsmentioning
confidence: 99%
“…BgArsM has A, B, and C domains as well as a linker­(D) between the A and B domains that contains 37 more residues than most other ArsMs (Figure and Figure S2). We previously reported that deletion of the additional residues restores As­(III) methylation, leading to the hypothesis that the extended linker modulates As­(III) methylation . This increases the rate of methylation of reduced AST-OH, which benefits host organisms for arsenical antibiotic biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenic (As) biomethylation is an important component of As biogeochemistry . Many organisms including some bacteria, archaea, fungi, algae, and animals are able to methylate inorganic arsenite [As­(III)] into different methylated As species such as monomethylarsenate [MMAs­(V)], dimethylarsenate [DMAs­(V)], and trimethylarsine [TMAs­(III)]. Enzymes catalyzing As biomethylation in microbes (arsenite S -adenosylmethionine methyltransferase, ArsM) and humans (AS3MT, As­(III) methyltransferase) have been identified and characterized. , Interestingly, higher plants such as rice, tomato, and red clover do not appear to be able to methylate As­(III) . Rice growing in flooded paddy soil often accumulates substantial amounts of methylated As species, especially DMAs­(V), in addition to inorganic As. These methylated As species are derived from microbial As biomethylation in soil, which is enhanced by soil flooding. DMAs­(V) is the most common methylated As species found in paddy soils. , Synthetic DMAs­(V) (also called dimethylarsinic acid or cacodylic acid) has also been widely used as a herbicide or defoliant in the past …”
Section: Introductionmentioning
confidence: 99%